DİNAMİK SİSTEMLERİN BOND GRAF MODELİ VE ENPORT SİMÜLASYONU - GÜLTEN, ARİF (Fırat Üniveristesi, 1996)
Yüksek Lisans Tezi" DİNAMİK SİSTEMLERİN BOND GRAF MODELİ VE ENPORT SİMÜLASYONU Arif GÜLTEN Fırat Üniversitesi Fen Bilimleri Enstitüsü Elektrik-Elektronik Mühendisliği Anabilim Dalı 1996, Sayfa: 42 Bu çalışmada, dinamik sistemlerin bond graf modelleri elde edilmiş ve bu modelleri kullanarak simülasyon yapan, ENPORT paket programı yardımıyla simülasyonlan gerçekleştirilmiştir. Simülasyon sonuçlarının bir kısmı farklı simülasyon metodlanyla elde edilen sonuçlarla, bir kısmı da deneysel sonuçlarla karşılaştırılmıştır. ANAHTAR KELİMELER: Bond graf, ENPORT

m SUMMARY Masters Thesis BOND GRAPH MODEL AND ENPORT SIMULATION OF DYNAMIC SYSTEMS ArifGÜLTEN Fırat University Graduate School of Natural and Applied Sciences Department of Electrical and Electronical Engineering 1996, Page: 42 In this work, bond graph models of dynamic systems are obtained and their simulation are realized by using ENPORT software which makes simulation by the help of these models. Some of the simulation results are compared to results, obtained from different simulation and some results are compared to experimental results. KEYWORDS: Bond graph, ENPORT
Keywords: Elektrik ve Elektronik Mühendisliği; Electrical and Electronics Engineering